Sealed endoscopic full-thickness resection for gastric cancer: a pilot study in an ex vivo and in vivo porcine model - Kitakata, Hidekazu; Itoh, Tohru; Kinami, Shinichi; Kawaura, Ken; Hamada, Kazu; Azukisawa, Sadafumi; Kobayashi, Rika; Kamai, Junji; Kosaka, Takeo (Endoscopy International Open, 2019)
Background and study aims Endoscopic full-thickness resection (EFTR) is a useful procedure that allows minimal resection of the gastric wall because the tumor can be located endoscopically. However, the procedure carries a risk of peritoneal infection or dissemination. Thus, we devised a new EFTR technique in which the serosa is sealed using a silicone sheet to prevent the escape of gastric juice.Materials and methods Three whole stomachs were harvested from pigs for an ex vivo experiment, and seven pigs were used for an in vivo experiment. In both experiments, silicone sheets and gauze were pasted to the serosa using a fibrinogen-thrombin solution. A seromuscular incision was then made endoscopically using a HookKnife. We then evaluated whether stomach collapse could be prevented using this technique. Furthermore, the method was compared with conventional laparoscopic-assisted EFTR (LA-EFTR) in terms of resection time and quality of endoscopic view.Results In the ex vivo experiment, stomach collapse was suppressed and the seromuscular layer could be incised layer by layer. In the in vivo experiment, the time required for seromuscular incision with the new EFTR technique was significantly shorter than that with the conventional method. All layers of the stomach were smoothly resected under good endoscopic view.Conclusions Sealed EFTR is a potentially useful technique for the minimally invasive resection of gastric tumor. All layers of the stomach could be incised while confirming the incision line from the inside of the stomach and avoiding exposure of the tumor to the abdominal cavity.